Lū Sipi: A Marker of Tongan Distinction - Neill, Lindsay; Toloke, Elizabeth (Waka Kuaka, 2021)
In Tonga, traditional dishes like lū sipi—lamb or mutton drenched in coconut cream and baked in taro leaves—play a crucial role in sustaining cultural norms, affirming place and constructing identity. Consequently, lū sipi illuminates daily routines and the significance of being and becoming Tongan. For Tongans abroad, lū sipi provokes island memories and nostalgia. Considering lū sipi’s importance both in Tonga and in Auckland, Aotearoa New Zealand, this paper explores lū sipi as a marker of Tongan distinction, using qualitative description, talanoa ‘Pasifika research methodology’ and thematic analysis. We interviewed two self-identifying Tongans and an academic expert on South Pacific Island culture, all based in Auckland. Their expertise and experiences, within our explorative research, provided a platform to understand lū sipi within Tongan culture, particularly its symbolic and actant properties. What our research reveals is that, despite its Tongan distinction, lū sipi reflects the dynamic nature of cultural change around food over both time and place. Within these considerations, our research explores the dynamic nature of food as an expression not only of the Tongan diaspora but of the dynamics of contemporary Tongan identity.